Sistem Pendukung Keputusan Menentukan Siswa Yang Menerima Beasiswa Menggunakan Metode SAW - Jamaludin Jamaludin; Agung Nugroho; Ikhsan Romli (Ikatan Ahli Informatika Indonesia, 2020)
The number of schools that are growing steadily, making the school is required to implement a better strategy. For that reason, the school must observe all the activities that exist in the school environment to be able to attract the attention of parents so that their children attend school. Decision Support System is basically to facilitate the school in selecting candidates who will receive scholarships, to get more accurate results, and apply the Simple Additive Weighting method. At SD Negeri Singajaya 03 the process of determining students who receive scholarships uses several criteria, namely Parental Income, Semester, Parental Dependency, Number of Brothers, and Value. In building this system the author uses the System Development Life Cycle (SDLC) development method, and for system design using the Unified Modeling Language (UML). For making the application the author uses PHP programming language and MYSQL database testing using the Black Box Testing method. The results of this study are an application of decision support to determine prospective scholarship recipients using the method Simple Additive Weighting (SAW). In conclusion, this Decision Support System is more convincing than the old method. Because the calculation results are faster, more efficient, and more accurate.